Question

\( 4 x^{2}-7 x y+4 y^{2}=16 \) and \( y=2 x-2 \)

Ask by Dawson Colon. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( (0, -2) \) and \( (3, 4) \).

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}4x^{2}-7xy+4y^{2}-16=0\\y-2x+2=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}4x^{2}-7xy+4y^{2}-16=0\\y=2x-2\end{array}\right.\) - step2: Substitute the value of \(y:\) \(4x^{2}-7x\left(2x-2\right)+4\left(2x-2\right)^{2}-16=0\) - step3: Simplify: \(6x^{2}-18x=0\) - step4: Factor the expression: \(6x\left(x-3\right)=0\) - step5: Separate into possible cases: \(\begin{align}&6x=0\\&x-3=0\end{align}\) - step6: Solve the equation: \(\begin{align}&x=0\\&x=3\end{align}\) - step7: Calculate: \(x=0\cup x=3\) - step8: Rearrange the terms: \(\left\{ \begin{array}{l}x=0\\y=2x-2\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=2x-2\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=0\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=4\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x=0\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=4\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right) = \left(0,-2\right)\cup \left(x,y\right) = \left(3,4\right)\) Solve the system of equations \( 4 x^{2}-7 x y+4 y^{2}-16=0; y=2 x-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}4x^{2}-7xy+4y^{2}-16=0\\y=2x-2\end{array}\right.\) - step1: Substitute the value of \(y:\) \(4x^{2}-7x\left(2x-2\right)+4\left(2x-2\right)^{2}-16=0\) - step2: Simplify: \(6x^{2}-18x=0\) - step3: Factor the expression: \(6x\left(x-3\right)=0\) - step4: Separate into possible cases: \(\begin{align}&6x=0\\&x-3=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=0\\&x=3\end{align}\) - step6: Calculate: \(x=0\cup x=3\) - step7: Rearrange the terms: \(\left\{ \begin{array}{l}x=0\\y=2x-2\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=2x-2\end{array}\right.\) - step8: Calculate: \(\left\{ \begin{array}{l}x=0\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=4\end{array}\right.\) - step9: Check the solution: \(\left\{ \begin{array}{l}x=0\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=4\end{array}\right.\) - step10: Rewrite: \(\left(x,y\right) = \left(0,-2\right)\cup \left(x,y\right) = \left(3,4\right)\) We have the following system of equations: 1. \( 4 x^{2} - 7 x y + 4 y^{2} = 16 \) 2. \( y = 2 x - 2 \) To solve this system, we can substitute the second equation into the first equation. ### Step 1: Substitute \( y \) in the first equation Substituting \( y = 2x - 2 \) into the first equation: \[ 4 x^{2} - 7 x (2x - 2) + 4 (2x - 2)^{2} = 16 \] ### Step 2: Expand and simplify Now, let's expand and simplify the equation: 1. Expand \( -7x(2x - 2) \): \[ -7x(2x - 2) = -14x^{2} + 14x \] 2. Expand \( 4(2x - 2)^{2} \): \[ 4(2x - 2)^{2} = 4(4x^{2} - 8x + 4) = 16x^{2} - 32x + 16 \] Now, substituting these back into the equation gives: \[ 4x^{2} - 14x^{2} + 14x + 16x^{2} - 32x + 16 = 16 \] ### Step 3: Combine like terms Combining like terms results in: \[ (4x^{2} - 14x^{2} + 16x^{2}) + (14x - 32x) + 16 = 16 \] This simplifies to: \[ 6x^{2} - 18x + 16 = 16 \] ### Step 4: Set the equation to zero Subtract 16 from both sides: \[ 6x^{2} - 18x = 0 \] ### Step 5: Factor the equation Factoring out \( 6x \): \[ 6x(x - 3) = 0 \] ### Step 6: Solve for \( x \) Setting each factor to zero gives: 1. \( 6x = 0 \) → \( x = 0 \) 2. \( x - 3 = 0 \) → \( x = 3 \) ### Step 7: Find corresponding \( y \) values Now, substitute these \( x \) values back into the equation \( y = 2x - 2 \): 1. For \( x = 0 \): \[ y = 2(0) - 2 = -2 \] So, one solution is \( (0, -2) \). 2. For \( x = 3 \): \[ y = 2(3) - 2 = 6 - 2 = 4 \] So, another solution is \( (3, 4) \). ### Final Solutions The solutions to the system of equations are: \[ (x, y) = (0, -2) \cup (3, 4) \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the given equations, start by substituting \( y = 2x - 2 \) into the quadratic equation \( 4x^2 - 7xy + 4y^2 = 16 \). This will allow you to express everything in terms of \( x \). After substituting, you will rewrite the quadratic equation in a standard form and then solve for \( x \) using appropriate methods, such as factoring or the quadratic formula. Once you have the values of \( x \), substitute them back into \( y = 2x - 2 \) to find the corresponding \( y \) values. Solving this system effectively gives you the points of intersection between the curve and the line, which may reveal some interesting relationships between the two entities and their geometric significance!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy